Expressive forms in Brahms's instrumental music : structure and meaning in his Werther quartet - Smith, Peter Howard (Musical meaning and interpretation., 2005)
"Johannes Brahms's dramatic Piano Quartet in C Minor, Opus 60, famously known as the Werther Quartet, forms the basis for Peter H. Smith's illuminating theoretical study. Throughout the book, Smith synthesizes the often-opposed approaches of Schenker and Schoenberg, discussing the interaction of different parameters (rhythm, form, key centers, etc.) in a "dimensional counterpoint," and addressing issues of expression in music - particularly those of tragedy and transcendence. Smith then extends his analysis beyond the isolated work, connecting the composer's approach in this piano quartet to comparable works by Brahms, and broadening the analysis to works of Beethoven and Mozart